DAMPAK PANDEMI COVID-19 TERHADAP PERKEMBANGAN DAN PROSPEK BPR DI KABUPATAEN SIMALUNGUN - DIAN G PURBA (JURNAL ILMIAH MAKSITEK, 2022)
The Covid-19 pandemic has spread to various countries, including Indonesia. The increasing number of Covid-19 cases weakens the national and international economy. Various business sectors experienced a slowdown due to the Covid-19 virus. The research uses descriptive qualitative research methods in which it is expected that economic and business actors related to this will show empathy and solidarity with stakeholders. Business people take advantage of and support the government's stimulus program. Rural Banks and other financial institutions must begin to improve their growth targets and the application of digital transaction technology in one solution. Economics and business can play a role in restoring bad things that have happened to the economy by prioritizing the achievement of goals.